In vitro culture of heliconia in different light sources - Takeui, Bruna; Ansante, Natalia Felipe; Rossi, Monica Lanzoni; Calaboni, Cristiane; Rodrigues, Paulo Hercílio Viegas (Plant Cell Culture & Micropropagation - ISSN 1808-9909, 2023)
The use of different light sources on in vitro culture, opens new perspectives for the micropropagation and the study of the effect on the explants. The aim of this study was to evaluate the effect of different combinations of LED light sources on the in vitro development of Heliconia orthotricha cuttings. Explants of the cultivar Total Eclipse were submitted to four subcultures in propagation culture medium (MS) and incubated under treatment with light sources as follows, B100: 100% blue; R100: 100% red; B70R30: 70% blue + 30% red; R70B30: 70% red + 30% blue; and the Control, with a white fluorescent lamp (WL). After the subcultures, the number of sprouts/shoots, height of seedlings, fresh mass and chlorophyll a, b and carotenoids were evaluated. Structural and ultrastructural changes were observed in the grouping of chloroplast thylakoid membranes, as well as an elongation of the hypodermal cells, and a reduction of leaf thickness in the treatment with a higher incidence of red light. The results demonstrated a reduction in the size of the cuttings produced in vitro, and an increase in productivity at the highest concentrations of red light incidence.